2007
DOI: 10.1117/1.2771553
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial reconstruction of retinal blood flow in three dimensions measured with high resolution resonant Doppler Fourier domain optical coherence tomography

Abstract: Resonant Doppler Fourier domain optical coherence tomography (FDOCT) is a functional imaging tool for extracting tissue flow. The method is based on the effect of interference fringe blurring in spectrometer-based FDOCT, where the path difference between structure and reference changes during camera integration. If the reference path length is changed in resonance with the Doppler frequency of the sample flow, the signals of resting structures will be suppressed, whereas the signals of blood flow are enhanced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…Asterisk represents the normal foveal bulge. SD OCT image of a 9-mm scan was obtained using Heidelberg Spectralis OCT with a custom scan acquisition protocol of up to 25 raster lines of 9 mm scan length with automatic real-time imaging set at 30 images can measure blood flow in the retinal and choroidal vessels [32]. Swept-source OCT can achieve ultrahigh axial resolution by sweeping a narrow bandwidth light source through a broad optical range [33].…”
Section: Further Advancesmentioning
confidence: 99%
“…Asterisk represents the normal foveal bulge. SD OCT image of a 9-mm scan was obtained using Heidelberg Spectralis OCT with a custom scan acquisition protocol of up to 25 raster lines of 9 mm scan length with automatic real-time imaging set at 30 images can measure blood flow in the retinal and choroidal vessels [32]. Swept-source OCT can achieve ultrahigh axial resolution by sweeping a narrow bandwidth light source through a broad optical range [33].…”
Section: Further Advancesmentioning
confidence: 99%
“…The Doppler angle (α) is the angle between the imaging beam and the absolute velocity vector of the blood (Fig. 2(c) is assumed that the flow is parallel with the vessel's orientation, the direction of the velocity vector can be estimated by acquiring a 3-D structural OCT volume of the vessel and measuring the vessel orientation [25,26]. However, the orientation can sometimes be difficult to determine in smaller blood vessels that are usually more tortuous and with borders that are difficult to discern.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the feasibility of quantifying blood°ow in vivo in the human retina, [18][19][20][21][22][23][24] skin, [25][26][27] brain, 28,29 and gastrointestinal tract, 30,31 as well as other locations. Doppler OCT (DOCT) combines the ability of OCT to captured high-resolution structural images with corresponding Doppler velocity maps that can be merged together to identify regions with moving re°ectors, indicating blood°ow.…”
Section: Introductionmentioning
confidence: 99%